Data embedding in high efficiency video coding (HEVC) videos by modifying the partitioning of coding units. Issue 11 (6th August 2019) - Shanableh, Tamer
Abstract : A data embedding solution in HEVC videos is proposed by modifying the partitioning of coding units (CUs). The partitions of a CU are first represented as a sequence of binary flags. The flags pertaining to 16 × 16 sub CUs are used as a cover for data embedding, where 6 or 4 message bits are embedded per CU. The data embedding algorithm guarantees that a maximum of one partition is modified per message segment, therefore, in a given CU, either 0, 1 or 2 partitions are modified. The proposed solution is assessed in terms of message payload, number of modified partitions, loss in video quality as indicated by the PSNR results, mean objective scores and excessive bitrate. The proposed solution can embed messages with up to an average payload of 32.6 kbit/s with a corresponding average distortion of <0.5 dB. Comparisons with existing solutions reveal that the proposed solution maintains similar message payloads with less modifications of CU partitioning and at the same time resulting in less distortions for the cover video.